Physical, Chemical, and Abrasion Properties of Aggregate and Sub-Base in Selected Quarries, Najaf, Middle of Iraq - Hiba Al-Khozaei; Muhsen Khalaf (Iraqi Geological Journal, 2022)
This research includes a study of the physical, chemical, and abrasive properties of selected quarries at quaternary period deposits in the Bahr Al-Najaf-Hassab valley, 35 km southwest of the Najaf. It aims to evaluate these properties corresponding with local and global specifications (American and British standards) for building, construction, and concrete work. The results of laboratory analyses of five sites, which include fine and coarse aggregates, such as sub-base, showed the accuracy of using aggregates for concrete work, according to the Iraqi standards, and in addition to where it was found, the first site is in class D, the second is in class B, and the third and fourth sites are in class C. As for the soft rubble, it is shown that the first, fourth, and fifth sites conform to the standard, so it can be concluded that most of the sites in the study area are exploited directly and that some treatments are carried out to keep the remainder for the purpose of exploitation.